Grafting and Budding in Yemane Gmelina arborea Roxb. - Arya, R. S.; Haque, M. S. (Indian Forester, 1982)
In Gmelina arborea Roxb. (Yemane) techniques on cleft grafting and patch budding were developed successfully at the Forest Genetics Nursery, New Forest, Dehra Dun. 100 per cent success was achieved using both the methods during the months of February, March and April. Bud grafts made in April 1979 flowered in the very next flowering season i.e., April, 1980. A few fruits were also collected from these plants which showed 40% germination. The grafts have also flowered for the successive seasons.